"A Symphony of Possibilities": The Joy of Art and Writing Through The Beat Within. Issue 3 (2nd October 2017) - Arthur, Deborah Smith
ABSTRACT: The Beat Within is a writing and art program and publication based in San Francisco that gives a voice to incarcerated youth in various locations across the country. This article recounts the experience of the partnership between a community-based learning course at Portland State University and juvenile detention in Multnomah County, Oregon, using The Beat Within as the means for prosocial interaction between university students and incarcerated youth. Included within the article are reflections from youth participants, university students, and the author about the power of the partnership.